Analytic keys for determination of squash and pumpkin cultivars - Rochelle, Luiz Antonio (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
Keys determining cultivars of squashes and pumpkins (Cucurbita mosohata Duch., Cueurbita maxima Duch., and Cucurbita pepo L.) based on stem and leaf characters are presented.